2016
DOI: 10.1016/j.jbtep.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Thought-shape fusion in young healthy females appears after vivid imagination of thin ideals

Abstract: Vivid imagination of thin ideals promoted by magazines results in impaired mood and BIS and moreover in body-related cognitive distortions (TSF-B) in healthy women, especially, for those with stronger ED symptomatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 36 publications
(55 reference statements)
4
26
0
Order By: Relevance
“…In contrast, the tendency to stick to such thoughts may favor pathological eating and body-related behavior. Since exposure to fattening foods and body ideals occur repeatedly on a daily basis, future studies should emphasize the role of cognitive processes, such as TSF, and especially focus on resulting behavioral consequences such as the urge to diet or frequent body checking (e.g., Coelho et al, 2008;Wyssen et al, 2016). Finally, a more profound knowledge about the effects of TSF and related cognitive inflexibility on ED pathology have the potential to further improve therapeutic interventions (such as ACT; Hayes et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the tendency to stick to such thoughts may favor pathological eating and body-related behavior. Since exposure to fattening foods and body ideals occur repeatedly on a daily basis, future studies should emphasize the role of cognitive processes, such as TSF, and especially focus on resulting behavioral consequences such as the urge to diet or frequent body checking (e.g., Coelho et al, 2008;Wyssen et al, 2016). Finally, a more profound knowledge about the effects of TSF and related cognitive inflexibility on ED pathology have the potential to further improve therapeutic interventions (such as ACT; Hayes et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that the susceptibility to TSF impacts self-related information processing and has emotional and behavioral consequences. While it has already been experimentally shown that in women food items (Coelho et al, 2008) and thin ideals (Wyssen et al, 2016) may provoke thought fusion linked to the experience of fear of weight gain, which leads to a vicious circle of negative affect and dysfunctional weight and shape regulation behavior, it has yet to be investigated, whether similar processes are present in men. Research is further needed to examine whether there are gender-specific triggers induce such cognitive processes and behavioral reactions in men (e.g., specific food items or muscularity ideals).…”
Section: Discussionmentioning
confidence: 99%
“…Effect sizes of parental criticism and of parental emotional overinvolvement on children's emotional eating were both small. Thus, in order to explain emotional eating in children, further child-, parent-or family-based variables such as emotion regulation abilities or cognitive distortions (Wyssen, Coelho, Wilhelm, Zimmermann, & Munsch, 2016) should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The manipulation was successful, in that the group with the fashion magazine reported induction of body-related cognitive distortions (e.g., feelings of fatness). Moreover, results showed a significant decrease of mood and body image satisfaction in the fashion magazine group compared to the control group ( Wyssen et al, 2016b ). The comparison process of an unrealistic inner thin-ideal representation with a preexisting negative representation of one’s own body (see e.g., Vossbeck-Elsebusch et al, 2015 ), might activate self-ideal discrepancy and lead to the feeling of weight gain.…”
Section: Introductionmentioning
confidence: 99%